2017
DOI: 10.5371/hp.2017.29.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cephalomedullary Nailing in Basicervical Fracture

Abstract: PurposeA basicervical femoral fracture is defined as a fracture of base of neck of femur that occurs medially from intertrochanteric line above lesser trochanter. In this study, we intended to evaluate radiological and clinical results of basicervical femoral fractures treated by intramedullary nailing.Materials and MethodsFifteen patients, who underwent intramedullary nailing among 50 patients, out of 50 who were diagnosed with basicervical femoral fractures from July 2012 to May 2015 were studied. All of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Basicervical proximal femoral fracture is a special type of fracture located in the intermediate border of intracapsular and extracapsular fracture. As a result, they have varying de nitions in the literature [10,11,17]. Due to its greater biomechanical instability and higher surgery failure rates, it's of signi cant importance to get proper diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basicervical proximal femoral fracture is a special type of fracture located in the intermediate border of intracapsular and extracapsular fracture. As a result, they have varying de nitions in the literature [10,11,17]. Due to its greater biomechanical instability and higher surgery failure rates, it's of signi cant importance to get proper diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The primary factors that predispose a patient with internal xation to poor prognosis include highly unstable fracture, inadequate reductions, improper xation chosen and poor rehabilitation strategy [17,18]. In addition, low bone density is an independent risk factor when treating with internal xation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Kweon et al . suggested that in the course of rehabilitation training, sitting should be allowed from the first postoperative day, and wheelchair usage and partial weight‐bearing was indicated between the 3rd and the 7th postoperative days, depending on the degree of reduction, systemic conditions, and pain.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports the treatment of basicervical fractures of the femur with CMN17181920). The success rate of treatment with CMN is wide range, from 45% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kweon et al19) reported CMN fixation for basicervical femoral fractures in elderly showed satisfactory results, considered to be a useful method if performed with skilled technique.…”
Section: Discussionmentioning
confidence: 99%